Mandatory day care for preschool children would not be an effective solution in targeting particular children - Sophia Schmitz; C. Katharina Spieß (DIW Weekly Report, 2018)
In Germany, around 94 percent of children between the ages of three and six attend a day care center. Regarding the remaining six percent, many experts have speculated that children, primarily those from socio-economically disadvantaged households, do not use day care. Based on data from the Socio-Economic Panel (SOEP) and the Families in Germany survey (FiD), the present study is one of the first representative studies to look at preschool children three and older who do not attend a day care center. The findings show that they are not necessarily from socio-economically disadvantaged homes. Some parents with high incomes and high levels of educational attainment also keep their children home or take advantage of other programs such as parent-child groups. For this reason, mandatory day care would not effectively target children from socio-economically disadvantaged households. Instead, parents who do not send their children to day care should be specifically informed of the advantages of day care attendance for their children, its costs, and possible exemptions from payment.
Keywords: I22; I24; I28; J13; 330; child care; non-attendance; early education; socio-economic differences